Host heterogeneity and unpredictability in parasite outbreaks - Jacob A. Cohen; Mark Viney; Andy Fenton (Proceedings of the National Academy of Sciences, 2026)
Experimental tests of the effects of host heterogeneities on parasite transmission are rare; previous studies focus on a single host trait over one generation of transmission. Thus, the long-term epidemiological consequences of interacting host heterogeneities remain unclear. We used a laboratory-based experimental system comprising the red flour beetle ( Tribolium castaneum ) infected with the eugregarine parasite, Gregarina cloptoni , to show, firstly, that two colonies of the beetle are heterogeneous in their susceptibility and infectiousness to the eugregarine. We then constructed experimental populations that differed in population-level heterogeneity in susceptibility and infectiousness by varying proportions of the colonies in the populations and tracked parasite transmission over eight weeks. We found that differences in parasite transmission among populations were explained by population mean susceptibility and infectiousness, rather than heterogeneity. Finally, to test the effects of heterogeneity on equilibrium parasite transmission we developed an agent-based model (ABM) for our host–parasite system. Results from our model showed that populations with the highest level of heterogeneity had the highest between-simulation variability in epidemiological measures. This demonstrated that even with the same starting conditions, host heterogeneities can drive high levels of uncertainty in epidemiological predictability. Our work presents a rare experimental assessment of how heterogeneities in susceptibility and infectiousness affect parasite transmission, showing that while these heterogeneities may not affect transmission directly, they can still affect epidemic variability, and hence predictability. This variability has considerable consequences for outbreak management strategies yet remains understudied, so further tests of the effects of host heterogeneity on epidemic variability will be important.